The Role Of Self-Confidence In Achieving Peak Performance : A Descriptive Quantitative Study Of Youth Basketball Athletes In Sukabumi - Mayangsari, Salamah; Boyke Mulyana, Raden; Nurmansyah Awwaludin, Patriana; Mulyana, Mulyana (Universitas Negeri Semarang, 2024)
This research seeks to examine the impact of self-confidence on the achievement of peak performance in youth basketball athletes. In addition to physical, technical, and tactical aspects, self-confidence is a crucial psychological factor that supports athletic success. It helps athletes manage competition pressure and boosts their readiness to perform at their best. The study employs a descriptive quantitative approach with a correlational design, involving 33 youth basketball athletes from Sukabumi City as participants. The instruments used include the Sports State Confidence Inventory (SSCI) to assess self-confidence and a peak performance questionnaire created by Garfield and Bennet. Data analysis was conducted using the Statistical Program for Social Sciences (SPSS) version 25, with results showing a significant positive correlation between self-confidence and peak performance, yielding a correlation value of 0.759 and a significance level of 0.000. These findings suggest that higher levels of self-confidence increase the likelihood of athletes reaching peak performance. This study aims to offer deeper insights into the factors that affect athletic achievement, particularly self-confidence, and contribute to future youth basketball athletes' development